PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SD NEGERI 62 PEKANBARU - Hermaiyulis Hermaiyulis; Hendri Marhadi; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to improve grade VA students mathematics learning achievemant at SD Negeri 62 Pekanbaru academic year 2014/2015 through “Application Of Model Problem Based Learning To Improve Grade VA Students Mathematics Learning Achievement At SD Negeri 62 Pekanbaru”. This research was conducted in March. The numbers of students are 28 students which contains of 16 boys and 12 girls. This research is classroom action research which contains of two cycles. Each cycle consist of 2 meeting. Parameter of the research is involve students learning achievement after the action in each cycle (daily test I, II). Instrument of the research contains of learning tools (syllabus, RPP, LKS, learning result paper sheet), observation of student and teacher activity sheet. Data of the research will analyse descriptively. Research data show that learning achievement has increased. Where prior to the application of the methods of model problem based learning as much as any 18 students (64,29%) scored daily test is above or equal to the minimum completeness criteria (KKM). It was improved to 71,43% after using the application of model problem based learning in first cycle. In the second cycle increased to 89,29%. Activities of the students during the learning process (I, II cycles) is can be categorized very well. From the explanation above shows that application of model problem based learning can be improving grade VA students mathematics learning achievement at SD Negeri 62 Pekanbaru.Key Words : problem based learning, students achievement mathematics